Psychosocial risk factors in university teachers - Heredia Gálvez, Sonnia A. (2018)
The psychosocial factors constitute a fundamental axis of the effects that work has on people’s lives. The present research applied the adaptation and validation of the “CoPsoQIstas 21” (short version) in the Ecuadorian environment. It was applied to 435 university professors to identify the level of psychosocial affectation that they are exposed in their context. The results showed that 72% of the participating teachers were located at a high level of exposure.